TYPES OF SPORTS SCHOOLS AND THEIR REGULATIONS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This comprehensive overview details the types of sports schools in Uzbekistan and their regulations. It highlights five primary categories: Children's and Youth Sports Schools (DYuSSh), Specialized Children’s and Youth Sports Schools of Olympic Reserve (SDYuShOR), Sports Internats (Boarding Schools), Higher Schools of Sports Excellence (VySSH), and Olympic Reserve Colleges. Each type of school serves a specific purpose, ranging from introducing young children to sports to preparing elite athletes for international competitions. The regulatory framework, governed by the Ministry of Physical Culture and Sports, includes criteria for admission, training programs, facilities, coaching standards, competition participation, support services, and funding. These regulations ensure high standards of training, safety, and athlete development, aiming to produce top-tier athletes capable of competing at the highest levels.